2021
DOI: 10.1186/s40645-021-00408-9
|View full text |Cite
|
Sign up to set email alerts
|

Application of Soil Water Index to landslide prediction in snowy regions: sensitivity analysis in Japan and preliminary results from Tomsk, Russia

Abstract: Soil Water Index (SWI) represents the conceptual water stored in the soil and is calculated using a three-layer tank model with hourly precipitation. In Japan, landslide disasters are likely to occur when SWI in an event exceeds the maximum value of the past 10 years; however, snowmelt-driven landslide disasters have not been considered yet. Using the tank model that simultaneously calculates SWI and runoff, we implemented the snowfall-accumulation-snowmelt processes into the original SWI and applied the modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…Although originally designed for river discharge analysis and warning systems, SWI calculation is also used for the case of soil water content in failure-prone slopes and consequent landslide disasters [7,14,16,28]. In Japan, the government uses SWI calculations along 60-min cumulative rainfall for a nationwide early-warning system for landslide disasters since March 2007.…”
Section: Soil Water Index (Swi) Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although originally designed for river discharge analysis and warning systems, SWI calculation is also used for the case of soil water content in failure-prone slopes and consequent landslide disasters [7,14,16,28]. In Japan, the government uses SWI calculations along 60-min cumulative rainfall for a nationwide early-warning system for landslide disasters since March 2007.…”
Section: Soil Water Index (Swi) Calculationmentioning
confidence: 99%
“…The system uses Radial Basis Function Network methods to analyze past records of SWI values and occurrence or non-occurrence of landslides, determining the lowest limit of SWI, known as the critical line, above which landslide occurrence is considered likely, and thus evacuation is advised [14]. These values are distributed in a 1-km mesh all throughout the Japanese territory and are found on the JMA website [28]. The critical SWI value for the study area of this research, at the time of the July 2018 disasters, was 124 mm.…”
Section: Soil Water Index (Swi) Calculationmentioning
confidence: 99%
“…A aplicação de índices derivados do Tank Model como indicadores conceituais do armazenamento de água no solo já é amplamente utilizada no Japão para avaliar a predisposição de ocorrência de inundações ou deslizamentos. Matsuyama et al (2021) aplicaram 2 índices derivados do Tank (SWI e SWI-modificado) em uma bacia hidrográfica na Rússia para previsão de deslizamentos acarretados por neve, com bons resultados. Outros trabalhos também foram bemsucedidos na estimativa deslizamentos (Lin et al, 2020) e estabilidade de encostas (Matlan et al, 2018).…”
Section: Total 61 61unclassified
“…Although the SWI and three-layer tank model are conceptual models, they are used in the Japanese sediment disaster warning system (Osanai et al 2010). Moreover, studies of the occurrence of landslides induced by heavy rainfall have demonstrated their effectiveness (Chen et al 2017;Matsuyama et al 2021;Saito et al 2010a;Shuin et al 2020).…”
Section: Introductionmentioning
confidence: 99%